SINTESIS SELULOSA DARI LIMBAH AMPAS TEBU (Saccharum Officinarum L.) DENGAN METODE HIDROLISIS ASAM DAN ULTRASONIKASI - Balqis Saniatul Mukarromah; Dina Kartika Maharani (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2025)
The annual increase in sugar factory production can lead to a yearly rise in bagasse waste. An alternative to minimize the increase in bagasse waste is to utilize it as nanocellulose. Bagasse contains 52.7% cellulose, 20% hemicellulose, and 24.2% lignin. The synthesis of nanocellulose was carried out using a combination of chemical and mechanical methods, namely acid hydrolysis and ultrasonication, resulting in a final yield of 39.96%. The FTIR spectra of raw bagasse and bagasse-derived nanocellulose showed changes indicating that the synthesis successfully removed non-cellulosic components such as lignin and hemicellulose. After the nanocellulose synthesis process, a small shoulder appeared at a 2θ angle of 14.5˚, indicating that the synthesis had successfully removed most of the amorphous structures such as lignin and hemicellulose. The nanocellulose from bagasse exhibited two diffraction peaks at 2θ angles of 16.2˚ and 22.2˚, which are characteristic of type I cellulose.